2019
DOI: 10.1186/s12913-019-4554-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electronic prescribing systems on healthcare professionals’ working practices in the hospital setting: a systematic review and narrative synthesis

Abstract: BackgroundThe aim of this systematic review was to synthesise peer-reviewed literature assessing the impact of electronic prescribing (eP) systems on the working practices of healthcare professionals (HCPs) in the inpatient setting and identify implications for practice and research.MethodsWe searched PubMed, Medline, Embase, Cochrane and the Cumulative Index to Nursing Allied Health Literature databases for studies published from inception to November 2018. We included controlled, uncontrolled, observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…Digital health tools have the potential to provide health care workers with a holistic view of patients’ medical conditions through access to their health-related data and improved communication, regardless of distance and access [ 5 ]. Furthermore, the use of digital technology in health care could potentially reduce turnaround times, resource use, medication errors, and adverse drug events; increase the use of preventive care; and enable greater adherence to clinical guidelines [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital health tools have the potential to provide health care workers with a holistic view of patients’ medical conditions through access to their health-related data and improved communication, regardless of distance and access [ 5 ]. Furthermore, the use of digital technology in health care could potentially reduce turnaround times, resource use, medication errors, and adverse drug events; increase the use of preventive care; and enable greater adherence to clinical guidelines [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As electronic prescribing was perceived to be more effective by respondents not currently using it, this may indicate optimism regarding the ability of electronic systems to reduce insulin prescribing errors in hospitals using paper‐based systems. In light of the current drive to implement electronic prescribing across all hospitals, we emphasize the need to carefully design and implement these systems in such a way that the potential benefits regarding insulin prescribing safety can be maximized, and the shortcomings, such as any negative impacts on healthcare professional working practices, can be minimized [26].…”
Section: Discussionmentioning
confidence: 99%
“…As described, changes to clinical workflow and working habits as a consequence of introducing EPR were also observed [ 15 , 21 , 36 , 37 ]. Researchers have often attributed negative changes to a lack of knowledge on the side of clinical management and software developers about best practices for workflows [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the availability of data such as real-time patient data as well as easier access to information [ 13 ] are also emphasized as benefits [ 14 ] and could result in increased patient’s safety [ 12 ]. Mohsin-Shaikh et al [ 15 ] noted improved readability, the possibility of remote access and reduced time for certain tasks, while Saranto and Kinnunen [ 16 ] demonstrated that the standardization from EPR produces more positive than negative effects concerning the documentation quality of nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation